Surgical treatment for duodeno-reno-cutaneous fistula - Kuo-Yang Hsi; Jiann-Ming Wu; Kuo-Hsin Chen (Formosan Journal of Surgery, 2018)
We report the case of a 58-year-old man diagnosed as having right renal stones and who had undergone shock wave lithotripsy several times. However, residual stones persisted and resulted in pyelonephritis and renal abscess. Percutaneous nephrolithotomy (PCNL) was performed. However, bile content discharge from the PCNL wound was observed later. Abdominal computed tomography revealed multiseptated right renal abscess with the right psoas muscle involvement and obscure plane between the right kidney and the duodenum. A fistulogram demonstrated the presence of duodeno-reno-cutaneous fistula. He underwent right nephrectomy and wedge resection of the duodenum for the closure of the fistula. The postoperative course was smooth, and the PCNL wound healed spontaneously during the admission. He remained asymptomatic 6 months after the operation. This report includes a literature review on the etiology, diagnosis, and treatment of the renoduodenal fistula.